Quality control and HPTLC analysis of a polyherbal Unani formulation Habb-i-Shahtara recommended for skin diseases (Indian Journal of Traditional Knowledge (IJTK), 2023)
The Unani system of medicine (USM) is one of the popular traditional systems of medicine. World widely, this system of medicine becomes an important health care system. Since many years back Unani medicines were used by the Unani physicians for treating the diseases ailments. In USM most of the drugs are of plant origin and their therapeutic effects are due to the presence of active phytochemicals. The proper standardization methods must be necessary for preparation of formulations otherwise secondary metabolites or active constituents might not be up to the quality. The standard operating procedures (SOP’s) are adopted for the preparation of Unani formulation. This study evaluated the quality of polyherbal unani formulation Habb-i-Shahtara, which is used in the treatment of skin diseases. The standardization parameters which were used for the development of quality standard of the study formulation were pharmacognostical studies, physicochemical and phytochemical parameters, HPTLC analysis, microbial load, aflatoxins, heavy metals and pesticide residues determination to evaluate the pharmacopoeial standard. The polyherbal Unani formulation Habb-i-Shahtara have been successfully standardized and the data and procedures which were used may serve the guidelines and standard reference in future for the preparation of formulation and for further study.